2019
DOI: 10.1039/c9dt01333d
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies of ene reactions between aminoborane (F3C)2BN(CH3)2and substituted propenes: additive effects on barriers and reaction energies

Abstract: Investigations of ene reactions between (F3C)2BNMe2 and substituted propenes reveal additive substitutional effects on barriers and reaction energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…"Average Substitution Corrections" (denoted ΔG ASC# ‡ for electronic and Gibbs free energy barriers and ΔG ASC# for Gibbs free energy reaction energies, with # representing the position of interest) were determined as previously described. 4 Briefly, a substitution correction is the difference between an energy (barrier or overall reaction) determined for a Diels−Alder reaction for a cyclopentadiene with a particular substitution pattern and the energy determined for the reaction involving the cyclopentadiene with that pattern but lacking the substituent in the position of interest. The Average Substitution Correction is the average of all such substitution corrections for a particular substituent at a particular position.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…"Average Substitution Corrections" (denoted ΔG ASC# ‡ for electronic and Gibbs free energy barriers and ΔG ASC# for Gibbs free energy reaction energies, with # representing the position of interest) were determined as previously described. 4 Briefly, a substitution correction is the difference between an energy (barrier or overall reaction) determined for a Diels−Alder reaction for a cyclopentadiene with a particular substitution pattern and the energy determined for the reaction involving the cyclopentadiene with that pattern but lacking the substituent in the position of interest. The Average Substitution Correction is the average of all such substitution corrections for a particular substituent at a particular position.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…We recently reported computational studies of pericyclic ene reactions between the dienophile (F 3 C) 2 B = NMe 2 , 1 , and all possible permutations of substituted propenes CR 1 R 2 CR 3 –CR 4 R 5 H (R = H, CH 3 , CF 3 , F) . Only one of these was predicted to be endothermic, and only a few combined small barriers with low exothermicities such that they might undergo retro-ene reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] From a molecular perspective, the FLP-type heterolytic activation of the H 2 takes place throughout electrostatic and molecular orbital interactions between the H 2 , LA and LB molecules. [11][12][13][14][15][16][17][18] In FLP chemistry, it is important that the LA and LB molecules have enough noncovalent interactions to form an initial encounter complex. Calorimetric and kinetic studies have shown that entropic effects play an essential role in the formation of the encounter complex.…”
Section: Introductionmentioning
confidence: 99%
“…From a molecular perspective, the FLP‐type heterolytic activation of the H 2 takes place throughout electrostatic and molecular orbital interactions between the H 2 , LA and LB molecules [11‐18] . In FLP chemistry, it is important that the LA and LB molecules have enough noncovalent interactions to form an initial encounter complex.…”
Section: Introductionmentioning
confidence: 99%